Bioethanol Production from Coconut Fiber Wastes using Saccharomyces Cerevisiae - Ilangarathna, D.A.; Kapilan, R. (University of Jaffna, 2022)
The principal energy source of the globe at present is non-renewable fossil fuels. With the arising of global dilemmas, the human population demands new energy sources. Coconut palm wastes have been identified as an important source of lignocellulosic biomass and it is underutilized in local industries, the accumulation of fiber has become a very problematic waste in Sri Lanka. Therefore, this study was aimed to determine the efficient coconut waste material for bioethanol production and to optimize the conditions for fermentation to enhance the yield. When the coconut husk fiber was inoculated with Saccharomyces cerevisiae (baker’s yeast 2g/L) in the fermentation media (100ml, 8o Brix, Waste extract: distilled water = 1:3) composed of 10 g/L yeast extract, 10 g/L KH2PO4, 2 g/L (NH4)2SO4, 2g/L peptone and 0.5 g/L MgSO4•7H2O and allowed for fermentation for 24h at 30oC and 100rpm, the ethanol yield was 0.8% V/V. When different coconut palm wastes such as mature leaves (old leaves), young leaves (green leaves), young fruit fiber (kurumba), roots and husk fiber were used as the substrate with Saccharomyces cerevisiae, significantly higher quantities of bioethanol were produced with young leaves (green leaves) and husk fibers. However, coconut husk fiber was selected as a bioethanol source, for further studies due to its abundance and availability in the farms, slow natural degradation, and its role in providing a breeding ground for mosquitoes. The conditions were optimized sequentially by changing one factor at a time while keeping the other variables constant. When the fermentation time was optimized with coconut husk fiber the ethanol yield was significantly increased by 4 times at the 3rd day, than non-optimized conditions. When the amount of coconut husk fiber was increased by 2.5 times (12.5g/ 100 ml), bioethanol output was significantly increased by 6.4 times. Ethanol yield was significantly increased when 3.75g/ 100ml of yeast inoculum was used, compared to the non-optimized condition (1.25g/ 100ml). When the pH of the media was optimized as 4.8, significantly higher bioethanol yield was obtained, than the control (3.8). When the solution (V): air space (V) ratio was optimized to 1:1.3, bioethanol output was significantly increased by 6.6 times compared with the non-optimized condition (1:4). Large scale multi-centre fermentation study needs to be done in order to determine commercialization.
Keywords: Baker’s yeast; Bioethanol; Coconut husk fiber; Fermentation; Optimization